Diet change and food loss reduction: What is their combined impact on global water use and scarcity?. Issue 3 (15th March 2016) - Jalava, Mika; Guillaume, Joseph H. A.; Kummu, Matti; Porkka, Miina; Siebert, Stefan; Varis, Olli
Abstract: There is a pressing need to improve food security and reduce environmental impacts of agricultural production globally. Two of the proposed measures are diet change from animal‐based to plant‐based foodstuffs and reduction of food losses and waste. These two measures are linked, as diet change affects production and consumption of foodstuffs and consequently loss processes through their different water footprints and loss percentages. This paper takes this link into account for the first time and provides an assessment of the combined potential contribution of diet change and food loss reduction for reducing water footprints and water scarcity. We apply scenarios in which we change diets to follow basic dietary recommendations, limit animal‐based protein intake to 25% of total protein intake, and halve food losses to study single and combined effects of diet change and loss reduction. Dietary recommendations alone would achieve 6% and 7% reductions of blue and green water consumption, respectively, while changing diets to contain less animal products would result in savings of 11% and 18%, respectively. Halving food loss would alone achieve 12% reductions for both blue and green water. Combining the measures would reduce water consumption by 23% and 28%, respectively, lowering water scarcity in areas with a population of over 600 million. At a global scale, effects of diet change and loss reduction were synergistic with loss reductions being more effective under changed diet. This demonstrates the importance of considering the link between diet change and loss reduction in assessments of food security and resource use. Key Points: Reducing animal products in diet increases effect of food loss reduction Together strategies reduce water consumption by 28% Combined strategies reduce water scarcity for over 600 million people